Research on Fault Feature Extraction Method for Hydroelectric Generating Unit Based on Improved FMD and CDEI - Tao Wu; Haipeng Gong; Zaiming Geng; Jian Deng; Fang Yuan (Energies)
As core pieces of equipment in hydropower generation, the operational condition of critical components such as the rotor and thrust bearing is crucial for the stability of hydropower units. The essence of fault diagnosis for hydroelectric generating units is pattern recognition. To achieve high recognition accuracy, it is necessary to maximize the distinguishability of different fault features. However, traditional time–frequency signal processing methods seldom consider this issue during the decomposition process, resulting in low sensitivity of the extracted features to different fault types. To address this issue, this paper proposes a fault feature extraction method for hydroelectric generating units based on Feature Modal Decomposition (FMD) and the Comprehensive Distance Evaluation Index (CDEI). By improving the FMD algorithm, the objective function for selecting modal components during the FMD decomposition process is set as the CDEI, which can measure the sensitivity of fault features, thereby enhancing the distinguishability of the obtained fault features. Next, the Distance Evaluation Index (DEI) is used to measure the sensitivity of the obtained features, and the most sensitive features are selected. Experiments using a rotor test bench and actual signals before and after thrust bearing horizontal adjustment from a hydroelectric generating unit were conducted and compared with related methods. The results show that the proposed method can effectively improve the sensitivity of the obtained fault features and achieve accurate fault diagnosis for hydroelectric generating units.